Comparison of executive functions of attention, observational learning functions and working memory - Arezoo Shahpiri; Hora Alirahmzadeh; Maryam Reyhani; Zeinab Amiri Moghadam (روانشناسی و روانپزشکی شناخت)
ntroduction: Professional sport not only requires physical preparation, technical and tactical factors, but also cognitive, psychological and emotional characteristics can affect performance. Objective: Hence, the objective of this study was to compare executive functions of attention, observational learning functions and working memory in professional athletes and ordinary people. Method: This is causal-comparative research. 90 people over 15 years old (45 professional athletes and 45 ordinary people) were included in this study during 2021-2022. For data collection, color-word Stroop test (… & … 2006), Functions of Observational Learning Questionnaire (FOLQ) (Cumming et al., 2005) and Working Memory Rating Scale (WMRS) were used. Data was analyzed using descriptive statistics and independent t-test. Results: The results of the t-test showed a significant difference between the variables of attention, observational learning functions and working memory between two groups of professional athletes and ordinary people (P<0.05). Accordingly, in all the variables of attention ability, observational learning functions including (skill, strategy and execution) and working memory, the mean score of the professional athletes group was higher than ordinary people (P<0.05). Conclusion: The study results showed the necessity of paying attention to executive functions of working memory, observational learning and sports activities; and many practical implications in the field of interventions for those who decide to exercise professionall